Isolamento e inoculação de bactérias diazotróficas e promotoras de crescimento em arroz irrigado - Nunes, Rosangela Silva Gonçalves (2013)
Brazil is one of the largest producers and consumers of rice (Oryza sativa) in the world, and the largest portion of its production comes from floodplain ecosystems, and Rio Grande do Sul (RS), the largest national producer. Rice production is dependent on nitrogen fertilizers, which have high costs and high capacity to pollute the environment. An alternative to reducing the application of nitrogen (N) is inoculated Diazotrophic able to promote biological fixation of nitrogen (BNF) and or, in rice plant growth. The aim of this study was to select and evaluate the efficiency of diazotrophic bacteria isolated from different rice varieties, and the potential contribution of BNF these isolates in the culture in question, under flooding conditions. Three studies were performed. In the first, we performed the isolation of diazotrophic bacteria present in 20 varieties of rice grown in RS. In the second, the isolates were tested for their ability to fix atmospheric nitrogen, produce and release acid-indole-3-acetic acid (IAA) and promote growth ten rice cultivars under conditions gnotobiotics. In the third study, an experiment was conducted in a greenhouse with four isolates that showed improved plant growth and the three cultivars responded more inoculation in vitro test. In tests with inoculation was used strain BR11417 (ZAE94 - Herbaspirillum seropedicae) as a reference. 35 isolates were obtained from roots and shoots of rice cultivars tested, and all showed the ability to fix atmospheric nitrogen and produce and release IAA in vitro. In the experiment under conditions gnotobiotics cultivars IRGA 409, Puita Inta-CL and Pampa cultivars proved more responsive to inoculation and isolates 12, 13, 29 were those who had higher plant growth promotion. In the greenhouse, the IRGA 409 was the one that responded to inoculation and isolated 12, who provided the greatest benefits in relation to plant tillering and dry matter production in rice cultivars studied.